Phenomenon of Demikhov.In the Sklifosovsky Institute (1960–1986).Research Coordination Council of the USSR Healthcare Ministry: Missed opportunities. Part 1 (1963) - S. P. Glyantsev (Трансплантология (Москва))
The article describes the key event for Soviet transplantology of the 1960, namely, the Meeting of the Presidium of the USSR Healthcare Ministry Council for the Coordination of Scientific Research and Implementation of the Scientific Achievements. The Meeting held on October 8, 1963, was initiated by V.P. Demikhov's letters addressed to Moscow City CPSU Committee and the USSR Healthcare Ministry. The attendees of the Meeting were 50 leading experts of the USSR in the field of surgery, immunology, and transplantology; the speakers at the Meeting were V.P. Demikhov as the principal speaker, and V.I. Burakovsky as the Chairman of the Committee that had studied V.P. Demikhov's proposals on the issue of organ transplantation and the prospects for scientific research in that area. V.P. Demikhov shared with the audience his ideas, which were well ahead of their time; and the Commission noted the perspective and complexity of the organ transplantation problem, proposing a number of measures to improve the existed situation.